Can we systematically review studies that evaluate complex interventions? - Sasha Shepperd; Simon Lewin; Sharon Straus; Mike Clarke; Martin P Eccles; Ray Fitzpatrick; Geoff Wong; Aziz Sheikh (PLoS Medicine)
Background to the debate The UK Medical Research Council defines complex interventions as those comprising "a number of separate elements which seem essential to the proper functioning of the interventions although the 'active ingredient' of the intervention that is effective is difficult to specify." A typical example is specialist care on a stroke unit, which involves a wide range of health professionals delivering a variety of treatments. Michelle Campbell and colleagues have argued that there are "specific difficulties in defining, developing, documenting, and reproducing complex interventions that are subject to more variation than a drug". These difficulties are one of the reasons why it is challenging for researchers to systematically review complex interventions and synthesize data from separate studies. This PLoS Medicine Debate considers the challenges facing systematic reviewers and suggests several ways of addressing them.